Kendala Implementasi Kebijakan Manajemen Risiko Multi Hazard di Pemerintahan Daerah: Studi Kasus Kota Bukittinggi - Muhammad Azlan ZM; Zikri Alhadi (PUBLICNESS: Journal of Public Administration Studies, 2026)
The implementation of multi-hazard disaster risk management policies at the local government level often encounters various constraints that affect policy effectiveness. This study aims to analyze the inhibiting factors in the implementation of multi-hazard risk management policies in Bukittinggi City. A qualitative approach with a case study design was employed, using interviews, observations, and documentation techniques, and analyzed through George C. Edward III’s policy implementation model. The findings indicate that the primary constraints include the absence of specific local regulations governing the multi-hazard approach, limited institutionalized coordination among local government agencies, insufficient human resource capacity and budget support, and inconsistent policy communication across institutions. In addition, the predominantly reactive orientation of policy implementation has hindered the integration of disaster risk reduction programs. These findings demonstrate that implementation constraints are multidimensional and require institutional strengthening and cross-sectoral policy integration to improve the effectiveness of disaster risk management at the local level.